Perceptions and attitudes toward palliative care among healthcare professionals in Qatar’s home care setting - Haddad, Feras; Day, Gary E.; George, Sybil; Sathian, Brijesh; Al-Hamad, Hanadi; Al-Sulaiti, Essa (Frontiers in Medicine, 2025)
IntroductionPalliative care (PC) is an emerging concept in the Middle East, with Qatar lacking formalized home-based services until the 2021 Doha declaration. This qualitative study addresses a gap in the literature by exploring home healthcare service (HHCS) staff perceptions, attitudes, and challenges in delivering PC in Qatar’s home setting, aiming to inform service development and enhance end-of-life care accessibility.MethodsUsing Braun and Clarke’s thematic analysis approach, semi-structured interviews were conducted with 13 purposively sampled HHCS staff from various disciplines (e.g., physicians, nurses, pharmacists). Interviews, lasting approximately 30 min each, were audio-recorded via Microsoft Teams, transcribed, and analyzed with QualCoder software to identify codes, sub-themes, and major themes.ResultsFour key themes emerged: (1) patient-centered care and comfort, emphasizing pain-free management, quality of life, and respecting patient/family wishes; (2) challenges and barriers, including narcotic drug access, community acceptance, and cultural/religious considerations; (3) communication and supportive services, highlighting clear channels and psychosocial/spiritual support; and (4) training and resources, stressing staff education, emotional support, and policy revisions.DiscussionFindings reveal unique Qatar-specific obstacles, such as regulatory restrictions on narcotics and cultural norms affecting death at home, while offering opportunities to improve training, policies, and awareness. These insights are crucial for integrating culturally sensitive PC into home-based systems, potentially reducing hospital burdens and aligning with global aging trends.